Redefining Paradiplomacy Strategy to Strengthen Island Governance Autonomy: The Case of Riau Islands, Indonesia - Muhammad Raka Hadiyan; Aulia Salvy Putri Maharani (Journal of Maritime Policy Science, 2024)
This research examines the role of paradiplomacy in strengthening the local governance autonomy of the Riau Islands, Indonesia, a region facing challenges in capitalizing on its strategic geographical location and marine resources. While Riau Islands holds significant potential in tourism, fisheries, and regional development, its subnational autonomy has not been fully leveraged to foster successful paradiplomatic initiatives. Using desk research and secondary data from governmental sources, scientific articles, and media reports, this study evaluates the effectiveness of paradiplomacy in enhancing regional cooperation, promoting sustainable development, and addressing socio-economic issues such as poverty and inequality. The findings reveal that, despite numerous successful collaborations with international non-governmental organizations (INGOs) and foreign governments, challenges remain in aligning local and national policies, managing external funds, and ensuring equitable distribution of resources. Empowering local communities, especially in the sectors of fisheries and tourism, has been a key focus, but issues of community displacement and foreign exploitation remain significant concerns. The research concludes that while paradiplomacy has contributed to some progress, a more coordinated and sustainable approach is necessary to fully realize the region’s potential. Future strategies should focus on enhancing local governance capacity, improving public-private partnerships, and fostering a more inclusive development model that ensures the benefits of paradiplomacy are widely distributed.